Case reportCerebral amyloid angiopathy manifested as a brain tumour. Clinical and neuropathological characteristics of two cases - Karbowniczek, Aleksandra; Wierzba-Bobrowicz, Teresa; Mendel, Tadeusz; Nauman, Paweł (Folia Neuropathologica, 2012)
We present two cases (female and male patients, aged 64 and 38, respectively) of focal mass lesions mimicking a brain tumour: one with cognitive function deficit, memory troubles, behavioral changes and left hemiparesis, the other with difficulty in orientation and right hemiparesis. General physical and neurological examinations, laboratory tests and neuroimaging were used to diagnose the cases. Both of them showed nonspecific changes in the brain tissue and the brain tumour was suspected. In the first case MRI scan revealed two pathological masses in the right frontal region and hemorrhagical focus with destructions inside lesions. Second patient’s MRI scan revealed a pathological mass at the interface of the left temporal and occipital regions. The neurosurgical procedure was performed. The final diagnosis was established on the basis of neuropathological examination of postoperative material. On light microscopy examination a severe cerebral amyloid angiopathy (CAA) was revealed. Amyloidoma was excluded due to the absence of amorphous material and eosynophylic masses. Tumefactive CAA is a rare condition. These two cases of focal, tumefactive, masslike lesions of diffuse cerebral amyloid angiopathy are reported because of diagnostic dilemmas. In patients with history of memory disfunction, neurological deterioration and different multiple changes observed in CT and MRI scans, such as hemorrhagic infarcts and ischemic cerebral lesions, CAA should be suspected. The imaging findings make a distinction between tumefactive CAA and brain tumours like gliomas difficult. A differential diagnosis of CAA and amyloidoma plays a significant role in a neuropathological examination.